The Importance of the Institution of Ombudsman in Protecting Human Rights by Initiating a Procedure of Review of the Constitutionality of Statutes - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Ombudsman authority disposes of an action before the Constitutional Court to review the constitutionality and legality of laws and other regulations. This competence is in the function of supplementing the general system of protection of the human rights. The exercise of this competence involves a systematic approach to the interpretation of the whole legal system, particularly the proper interpretation of constitutional norms and values that they protect (including human rights as an essential value). Thus, in effect, the Ombudsman achieves a major share in the overall system of protection of the rights of citizens and raising awareness of  their importance in modern society. This, in effect, defines the real measure of the impact of this institution in the general system of protection of human rights in our country.
Keywords: the Constitution of the Republic of Serbia; constitutional dispute; constitutionality and legality; protection of citizen’s rights; Protector of citizens